Efektivitas Penggunaan TikTok sebagai Media Edukasi terhadap Pengetahuan Remaja dalam Persiapan Pernikahan - Yulianita, Fani; Hiola, Fidya; Umar, Siskawati; Abas, Mohamad Ilyas (STIKes Hamzar, 2025)
Marriage is one of the important steps in human life that binds men and women as husband and wife. There are regulations that setthe ideal age limit for marriage. However, there is still a high rate of early marriage dispensation. In line with technological developments, social media has become a means of information and education, TikTok is a social media platform that is trendingamong adolescents and has great potential as a means of education. This study aims to determine the effectiveness of using TikTok as an educational medium for adolescent knowledge in preparing for marriage at SMA Negeri 1 Gorontalo. This type of research is quantitative research using Quasi-experimental with a one group pretest-posttest design. The research sample was 41 class XII students at SMA Negeri 1 Gorontalo who were selected using the purposive sampling technique. The instrument used was a pretestand posttest questionnaire that had been tested for validity and reliability. Data analysis was carried out univariately and bivariately using the Wilcoxon Signed rank test. The results of the study showed a significant increase in adolescent knowledge after being given education through TikTok videos for six days, with a significance value of p = 0.000 (<0.05). It can be concludedthat TikTok media is effective as a means of education in increasing adolescent knowledge about marriage preparation. It is hoped that this study can be considered as a premarital education strategy in marriage preparation.